Cold Spring Harbor Laboratory 2022: emerging insights and viewpoints in immunology. Issue 4 (April 2023) - Kagan, Jonathan C.; Rothenberg, Ellen V.; Weiss, Arthur; Rudensky, Alexander Y.; Smale, Stephen T.
Abstract: Some of the current and former organizers of the Cold Spring Harbor Laboratory (CSHL) 'Gene Expression and Signaling in the Immune System' (GESIS) meeting offer opinions on emerging questions in immunology, discussing the strong value of this recurring scientific meeting in the field.